Corporate diplomacy building reputations and relationships with external stakeholders - Henisz, Witold J. (Routledge, 2017)
Managers of multinational organizations are struggling to win the strategic competition for the hearts and minds of external stakeholders. These stakeholders differ fundamentally in their worldview, their understanding of the market economy and their aspirations and fears for the future. Their collective opinions of managers and corporations will shape the competitive landscape of the global economy and have serious consequences for businesses that fail to meet their expectations. This important new book argues that the strategic management of relationships with external stakeholders - what the author calls "Corporate Diplomacy" - is not just canny PR, but creates real and lasting business value.Using a mix of colourful examples, practically relevant tools and considered perspectives, the book hones in on a fundamental challenge that managers of multinational corporations face as they strive to compete in the 21st century. As falling communication costs shrink, the distance between external stakeholders and shareholder value is increasingly created and protected through a strategic integration of the external stakeholder facing functions. These include government affairs, stakeholder relations, sustainability, enterprise risk management, community relations and corporate communications. Through such integration, the place where business, politics and society intersect need not be a source of nasty surprises or unexpected expenses. Most of the firms profiled in the book are now at the frontier of corporate diplomacy. But they didn't start there. Many of them were motivated by past failings. They fell into conflicts with critical stakeholders - politicians, communities, NGO staffers, or activists - and they suffered. They experienced delays or disruptions to their operations, higher costs, angry customers, or thwarted attempts at expansion. Eventually, the managers of these companies developed smarter strategies for stakeholder engagement. They became corporate diplomats. The book draws on their experiences to take the reader to the forefront of stakeholder engagement and to highlight the six elements of corprate diplomacy.